An Inexpensive Method for Producing Oxygen Deficiency in Thin Films of WO3 and Their Characterization with the Help of Electrical Properties - Sharan, M.K.; Prasad, G.N.; Shah, V.N. (Asian Journal of Chemistry, 2010)
In the present work we describe the method for producing oxygen deficiency in thin films of WO3 and their characterization.